2012
DOI: 10.3233/jem-120364
|View full text |Cite
|
Sign up to set email alerts
|

Does it matter how happiness is measured? Evidence from a randomized controlled experiment

Abstract: A continuous and a discrete rating scale were implemented for a single item happiness question in a representative survey. A randomized controlled experiment enables unique analyses on data quality and distributions, which suggest superiority of the continuous scale. Results raise doubts about earlier inferences drawn on correlates of happiness. So far only self-assessed discrete happiness data have been used for research into the determinants of happiness. However, distribution distortions were found for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…This study provides further evidence that VAS are feasible in web surveys (e.g., Funke & Reips, 2012b;Studer, 2012). Although sliders and VAS look similar, they affect the data collection process differently.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This study provides further evidence that VAS are feasible in web surveys (e.g., Funke & Reips, 2012b;Studer, 2012). Although sliders and VAS look similar, they affect the data collection process differently.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, VAS' fine gradations are especially valuable in semantic differentials or polarity profiles, where VAS can help to avoid the problem of shared ranks (see Funke & Reips, 2012b). Studer (2012) found that VAS are feasible in web surveys and suited for measurement of happiness without scaling effect. VAS can either be realized as continuous scales (each pixel in length serves as a possible rating) or be realized as discrete n-point scales.…”
mentioning
confidence: 98%
“…Admittedly, there is no conceptual model that specifies what metric is best for measuring approval, and no consensus exists on how to best to measure it in experimental studies of audience costs (Tomz (2007) and Levy et al (2015) use a 7-point scale; Levendusky and Horowitz (2012) use a 5-point one). I chose an 11-point scale as there is some evidence that more continuous measures provide more information than discrete Likert scales by overcoming endpoint aversion (Studer, 2012). The second measure I used was the difference in executive approval after a coercive foreign policy threat was made and after the executive reneged on this threat.…”
Section: The Experimentsmentioning
confidence: 99%
“…The multi-item questionnaires are better tools at capturing subjective wellbeing (Helm 2000). At this stage in the development of wellbeing/happiness measurements the discrete rating scale is widely accepted with some efforts at creating a continuous measure (Studer 2012).…”
Section: Methodsmentioning
confidence: 99%